Ungovernable, Incorrigible, and Impudent: An Empirical Study of Criminal Character Among Serious Institutionalized Delinquents - Slemaker, Alexandra (American journal of criminal justice, 2023)
The notion of criminal character—indicative of an offender unresponsive to rehabilitative efforts, largely unamenable to treatment, primed for recidivism, and committed to a criminal or delinquent lifestyle—has an uneven history in criminology and criminal justice. Despite tangential efforts to apply criminal character considerations to delinquency, we are unaware of any study that has empirically employed the concept of criminal character among justice-system involved youth. Here, we examine the similarities and differences among a large cohort of serious delinquent offenders, some of whom correctional staff assessed as having "criminal character." Youth with criminal character had more extensive delinquent history, adverse childhood experiences, psychopathology, and institutional and violent misconduct while confined in state juvenile correctional facilities and had significant associations with institutional and violent misconduct despite controls for 29 covariates. However, sensitivity analyses indicated the results were sensitive to specification of the dependent variable (e.g., null associations with dichotomous measures of misconduct) and revealed period effects (e.g., null associations for more recently placed youth). Our models show the potential pitfalls from using administrative measures of criminological and forensic concepts and we offer guidance for measurement development in this area.